2014
DOI: 10.1089/hgtb.2014.093
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Production of Dual Recombinant Adeno-Associated Viral Vectors for Factor VIII Delivery

Abstract: Recombinant adeno-associated viral (rAAV) vectors have gained attention for human gene therapy because of their high safety and clinical efficacy profile. For factor VIII gene delivery, splitting the coding region between two AAV vectors remains a viable strategy to avoid the packaging capacity limitation (*5.0 kb). However, it is time-consuming and labor-intensive to produce two rAAV vectors in separate batches. Here we demonstrated successful production of dual rAAV vectors for hemophilia A gene therapy in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 41 publications
1
36
0
Order By: Relevance
“…17,23,25,26,29,35 The AAV particles purified from these bands were reported to have significantly different infectious properties in vitro. De la Maza and Carter found a 16-fold difference in infectivity between the regular and heavy AAV2 particles, 17 whereas Roy et al reported a 300-fold difference in infectivity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…17,23,25,26,29,35 The AAV particles purified from these bands were reported to have significantly different infectious properties in vitro. De la Maza and Carter found a 16-fold difference in infectivity between the regular and heavy AAV2 particles, 17 whereas Roy et al reported a 300-fold difference in infectivity.…”
Section: Discussionmentioning
confidence: 99%
“…35 Briefly, pAAV-Rep&Cap (serotype 8), pAd helper, and the transgene plasmids were cotransfected into HEK 293 cells cultured in roller bottles at a ratio of 1:1:1. Vectors from both the transfected cells and medium were harvested 72 h post transfection, and purified by two rounds of CsCl gradient ultracentrifuge.…”
Section: Production and Purification Of Raav Vectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Briefly, human Huh7 cells were transduced with 1 · 10 3 vg/cell with QM-ssAAV2-WT-Fluc, QM-ssAAV2-LC1-Fluc, QM-ssAAV2-LC2-Fluc, DM-ssAAV3-WT-Fluc, DMssAAV3-LC1-Fluc, or DM-ssAAV3-LC2-Fluc vectors and incubated for 72 hr. Transgene expression was determined by Luciferase Assay System (mean -SD) as described previously.…”
Section: Recombinant Aav Vector Transduction Assays In Vitromentioning
confidence: 99%